Experimental and Numerical Study on Air Flow Behavior for a Novel Retractable Reverse Circulation Drill Bit of Casing-while-Drilling (CwD). (21st August 2021) - Qi, Bo; Cao, Pinlu; Yang, He; He, Wenbo; Wang, Mengke; Chen, Baoyi; Bo, Kun; Zheng, Zhichuan
Abstract : A reverse circulation Down-The-Hole (DTH) hammer drill bit in Casing-while-Drilling (CwD) processes is designed and applied to drilling under complicated formation. The drill bit is a special retractable drill bit with an exclusive reverse circulation gas channel. Using numerical simulations and experiments, the influence of the gas channel structure parameters of the drill bit, including the inner jet nozzles, flushing nozzles, suction channel, and other parameters, on its reverse circulation performance is analyzed, and the optimal gas channel structure parameters of the drill bit are determined to improve the reverse circulation effect. The results show that the flushing nozzles and inner jet nozzles have an important influence on entrainment performance. The entrainment rate η decreases as the flushing nozzle diameter increases and decreases as the inner jet nozzle diameter increases. An increase in the suction channel diameter can improve the reverse circulation effect of the drill bit. The spiral slot drill bit is more conducive to air being sucked into the central channel in the form of spiral flow, so it can improve the entrainment performance. The entrainment rate η can reach 23.4% with the optimum structured drill bit.